Serum lactate dehydrogenase is a more useful biomarker of prognosis than serum S100B in patients with BRAF‐mutant melanoma. (1st April 2016) - Sullivan, R.J.
Abstract: Linked Article: Frauchiger et al. Br J Dermatol 2016; 174 : 823–830 .